Multi-criteria ranking of available forms of promotional activities: a case analysis - Rajkovic, Jelena; Postin, Jasmina; Konjikusic, Marko; Jagodic Rusic, Aleksandra; Nikolic, Milan (Anali Ekonomskog fakulteta u Subotici, 2020)
This paper presents an analysis of the case of multicriteria choice of promotion form for a product group, in one large retail chain. The following forms of promotion were available: commercial propaganda, personal selling, sales promotion, publicity, public relations and direct marketing. The selection was made on the basis of five criteria: the effects of a given form of promotion, the costs of a given form of promotion, the compliance of a given form of promotion with consumer preferences, the appropriateness of a given form of promotion in relation to the promotion of competition and the engagement of human resources for a given form of promotion. The problem of multicriteria analysis was solved with the VIKOR method. The initial decision table and criteria weights were determined using the expert method, in which the opinions of ten experts from the observed company were taken. In this way, subjectivity in these initial procedures is reduced. The expert method and the VIKOR method proved to be very suitable in the given situation. The final conclusion is that in the promotion of the analyzed product group, publicity should be used to the fullest extent possible, economic propaganda should be applied in accordance with financial possibilities, and most attention and energy should be directed towards sales promotion activities.